Konseling Islami Untuk Meningkatkan Efikasi Diri Pasien HIV/AIDS - Dina Hajja Ristianti (Universitas Mathla'ul Anwar Banten, 2018)
ISLAMIC COUNSELING TO IMPROVE SELF EFFICACY OF HIV/AIDS PATIENTS. HIV/AIDS sufferers show low self efficacy that causes hypochondria which people often think about loss, loneliness and sinful feelings above all of what has been done. This causes them less emphasis on health care. Implementation of the value of Islamic religion in counseling or called Islamic counseling is very important to do because of a strong relationship between religious Islam with increase self-efficacy. This study wanted to know how self efficacy of HIV/AIDS sufferers in Rejang Lebong Regency can be improved by Islamic counseling. This research was conducted in clinic VCT RSUD Curup Rejang Lebong with the counselor as the key informant.Triangulasi is done by interviewing doctor hwo is handling patient and also companion of peer (PS). Data collection is done by interview and documentation. Futuremore the data is analyzed by doing data reduction, data presentation and conclusion and meaning. The result of research shows that Islamic Counseling is done by counselor on post test counseling by giving advice concerning Allah's greatness, His forgiveness and taubatan nashuhah that bring the patient becomes more resilient, anthusiastict with the process of treatment, more eager to fulfill worship and dayly activity.